Jack Aviv and brains of children. Issue 8 (4th December 2017) - Lamola, Angelo A.
Abstract: Both lead intoxication in early childhood and deficient bilirubin‐binding capacity (BBC) of blood in jaundiced neonates indicate risk for brain damage. Zinc protoporphyrin (ZPP) is a biomarker for lead intoxication (PbI) as well as well as for iron deficiency. Under the leadership of Jack Aviv, Aviv Biomedical, Inc. developed robust hematofluorometers for point‐of‐care assays of ZPP in blood and for the high‐affinity BBC of blood. These assays use just drops of whole blood and are simple, fast and inexpensive. ZPP by hematofluorometry has been used world‐wide as a primary screen for lead intoxication since 1979. Recent clinical studies enabled by an Aviv Biomedical, Inc. bilirubin hematofluorometer have renewed interest in BBC‐based assessment of neurotoxicity for improved management of neonatal jaundice. This article sketches Jack Aviv's contribution to the development and application of hematofluorometry. Abstract :